Microwave-assisted synthesis of Ag–TiO2/graphene composite for hydrogen production under visible light irradiation. Issue 16 (December 2016) - Khalid, N.R.; Ahmed, E.; Ahmad, M.; Niaz, N.A.; Ramzan, M.; Shakil, M.; Iqbal, T.; Majid, A.
Abstract: Novel photocatalysts based on silver (Ag), TiO2, and graphene were successfully synthesized by microwave-assisted hydrothermal method. The prepared photocatalysts were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) specific surface area analysis, X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy (EIS). The influence of silver loading and graphene incorporation on photocatalytic hydrogen (H2 ) production of as-prepared samples was investigated in methanolic aqueous solution under visible light irradiation (λ≥420 nm). The results showed that Ag–TiO2 /graphene composite had appreciably enhanced photocatalytic H2 production performance under visible light illumination compared to pure TiO2, Ag–TiO2 and TiO2 /graphene samples. The enhanced photocatalytic hydrogen production activity of Ag–TiO2 /graphene composite under visible light irradiation could be attributed to increased visible light absorption, reduced recombination of photogenerated charge carriers and high specific surface area. This novel study provides more insight for the development of novel visible light responsive TiO 2− graphene based photocatalysts for energy applications.